Dynamic adsorption of octanols at air/water interface - Phan, Chi (Wiley-Blackwell Publishing, Inc., 2010)
The dynamic adsorptions of 1-, 2- and 3-octanols at air/water interface were monitored using pendant drop method. It has been found that 1-octanol had strongest interfacial effects, yet slowest rate of adsorption. The experimental data were compared with diffusion-controlled and diffusion-kinetic-mixed models. Excepting 3-octanol at 1 mM, all systems required kinetic step. The effective kinetic constant was found varying with the concentration and the carbinol position. The results highlighted the influence of hydrophobic tails on the dynamic adsorption.